Comparison Studies of Reading Readiness Skills Acquisition by Different Methods: Formal Reading Readiness Program, Informal Reading Readiness Program, and a Kindergarten Science Program. - Quorn, Kerry Charles; Yore, Larry Dean (Science Education)
The article discusses on two experiments that examines the efficiency of Science: A Process Approach, Part A (SAPA) and The First Talking Alphabet, which are to not similar education program, and assess the effects of these programs, and two other programs namely informal language development program and control in kindergarten pupils from schools near Victoria, British Columbia. Through these experiments, the authors explain that those programs cannot support the effectiveness of reading development of kindergarten science students.